2013
DOI: 10.1002/aur.1300
|View full text |Cite
|
Sign up to set email alerts
|

Association between MTHFR Gene Polymorphisms and the Risk of Autism Spectrum Disorders: A Meta‐Analysis

Abstract: Methylenetetrahydrofolate reductase (MTHFR) is essential for DNA biosynthesis and the epigenetic process of DNA methylation, and its gene polymorphisms have been implicated as risk factors for birth defects, neurological disorders, and cancers. However, reports on the association of MTHFR polymorphisms with autism spectrum disorders (ASD) are inconclusive. Therefore, we investigated the relationship of the MTHFR polymorphisms (C677T and A1298C) and the risk of ASD by meta-analysis. Up to December 2012, eight c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
76
0
12

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(95 citation statements)
references
References 30 publications
6
76
0
12
Order By: Relevance
“…In our study, a positive association was observed between MTHFR C677T variant allele and autism risk. Our observation supports the meta-analysis data reported by Pu et al [47]. Another study by Mohammad et al [23] of the MTHFR C677T polymorphism in Indian patients with specific neurological pathologies has indicated that there was significant association with children associated with Autism.…”
Section: Discussionsupporting
confidence: 82%
“…In our study, a positive association was observed between MTHFR C677T variant allele and autism risk. Our observation supports the meta-analysis data reported by Pu et al [47]. Another study by Mohammad et al [23] of the MTHFR C677T polymorphism in Indian patients with specific neurological pathologies has indicated that there was significant association with children associated with Autism.…”
Section: Discussionsupporting
confidence: 82%
“…Results of several recent studies, including the prospective study by Surin et al [8] are encouraging, but it is too early to say that universal periconceptional use of folic can reduce the incidence of ASD resulting from abnormal folate-methionine metabolism. Some very recent epigenetic studies in monozygotic twins provide support for potential role of DNA methylation via a high maternal folic acid intake in ASD [19,20]. Specifically, findings by Wong and colleagues [20] are provocative and provide support for a potential role of DNA methylation via a high maternal folic acid intake in ASD and ASD-related traits.…”
Section: Discussionmentioning
confidence: 97%
“…DNA methylation defects are associated with ASDs, and MTHFR and its role in folate metabolism may contribute to epigenetic mechanisms that modify complex gene expression causing autism [26]. The association of SHANK3, methionine synthase (rs1805087) and contactin-associated-like 2 (CNTNAP2) gene polymorphism in a population in northern Iran has been demonstrated [27][28][29].…”
Section: Discussionmentioning
confidence: 99%